Superhydrophobic ZnO Nanocoatings for Different Substrates - Wang, Yanfen; Li, Benxia; Xu, Chuyang; Nie, Rongchun (Asian Journal of Chemistry, 2013)
Much attention has been paid to the superhydrophobic nanocoatings due to their many advantages, such as low adhesion, low friction and high restitution coefficient. Herein, we introduce a facile approach for the fabrication of superhydrophobic nanocoating using functional ZnO nanocrystals on the different substrate materials. Through a simple dipping and coating method, the resulting coatings display a remarkable superhydrophobic property with high contact angle.